Connective tissue growth factor regulates adipocyte differentiation of mesenchymal stromal cells and facilitates leukemia bone marrow engraftment - Battula, V. Lokesh (American Society of Hematology, 2013)
Mesenchymal stromal cells (MSCs) are a major component of the leukemia bone marrow (BM) microenvironment. Connective tissue growth factor (CTGF) is highly expressed in MSCs, but its role in the BM stroma is unknown. Therefore, we knocked down (KD) CTGF expression in human BM-derived MSCs by CTGF short hairpin RNA. CTGF KD MSCs exhibited fivefold lower proliferation compared with control MSCs and had markedly fewer S-phase cells. CTGF KD MSCs differentiated into adipocytes at a sixfold higher rate than controls in vitro and in vivo. To study the effect of CTGF on engraftment of leukemia cells into BM, an in vivo model of humanized extramedullary BM (EXM-BM) was developed in NOD/SCID/IL-2rg(null) mice. Transplanted Nalm-6 or Molm-13 human leukemia cells engrafted at a threefold higher rate in adipocyte-rich CTGF KD MSC-derived EXM-BM than in control EXM-BM. Leptin was found to be highly expressed in CTGF KD EXM-BM and in BM samples of patients with acute myeloid and acute lymphoblastic leukemia, whereas it was not expressed in normal controls. Given the established role of the leptin receptor in leukemia cells, the data suggest an important role of CTGF in MSC differentiation into adipocytes and of leptin in homing and progression of leukemia.